Noodle soup : recipes, techniques, obsession - Albala, Ken, 1964- (University of Illinois, 2018)
Every day, noodle shops around the globe ladle out quick meals that fuel our go-go lives. But Ken Albala has a mission: to get YOU in the kitchen making noodle soup. This primer offers the recipes and techniques for mastering quick-slurper staples and luxurious from-scratch feasts. Albala made a different noodle soup every day for two years. His obsession yielded all you need to know about making stock bases, using dried or fresh noodles, and choosing from a huge variety of garnishes, flavorings, and accompaniments. He lays out innovative techniques for mixing and matching bases and noodles with grains, vegetables, and other ingredients drawn from an international array of cuisines. In addition to recipes both cutting edge and classic, Alabala describes new soup discoveries he created along the way. There's advice on utensils, cooking tools, and the oft-overlooked necessity of matching a soup to the proper bowl. Finally, he sprinkles in charming historical details that cover everything from ancient Chinese millet noodles to that off-brand Malaysian ramen at the back of the ethnic grocery store. Filled with more than seventy color photos and one hundred recipes, A World of Noodle Soup is an indispensable guide for cooking, eating, and loving a universal favorite.